An Updated Review and Meta Analysis of Lipoprotein Glomerulopathy - Li, Meng-shi; Li, Yang; Liu, Yang; Zhou, Xu-jie; Zhang, Hong (Frontiers in Medicine, 2022)
More than 200 cases of lipoprotein glomerulopathy (LPG) have been reported since it was first discovered thirty years ago. Although relatively rare, LPG is clinically an important cause of nephrotic syndrome and end-stage renal disease. Mutations in the APOE gene are the leading cause of LPG. APOE mutations are an important determinant of lipid profiles and cardiovascular health in the population and can precipitate dysbetalipoproteinemia and glomerulopathy. Apolipoprotein E-related glomerular disorders include APOE2 homozygote glomerulopathy and LPG with heterozygous APOE mutations. In recent years, there has been a rapid increase in the number of LPG case reports and some progress in research into the mechanism and animal models of LPG. We consequently need to update recent epidemiological studies and the molecular mechanisms of LPG. This endeavor may help us not only to diagnose and treat LPG in a more personized manner but also to better understand the potential relationship between lipids and the kidney.